Hyperbaric oxygen in the treatment of calciphylaxis: A case series and literature review. (July 2015) - An, Jennifer; Devaney, Bridget; Ooi, Khai Yang; Ford, Sharon; Frawley, Geoff; Menahem, Solomon
Abstract: Aims: Calcific uraemic arteriolopathy (CUA) or calciphylaxis is most commonly seen in end‐stage renal disease and is associated with significant morbidity and mortality. The aim of this study was to determine whether hyperbaric oxygen therapy (HBOT) is effective in healing calciphylaxis lesions and to determine if there are any patient factors that can predict wound healing and patient survival. Methods: We identified by retrospective review all cases of CUA referred to our institution for treatment with HBOT. We documented the clinical and biochemical parameters of this patient population, the size and distribution of the lesions as well as wound outcomes and patient survival following treatment. Results: A total 46 patients were identified with CUA associated with renal failure. Of the 46 patients, only 34 received a full course of HBOT. The balance was deemed unsuitable for treatment or was unable to tolerate treatment and was palliated. Of the 34 patients that received a full course of HBOT, 58% showed improvement in their wound scores, with more than half of these patients having complete healing of their wounds. The balance did not benefit from the therapy and had a very poor prognosis. Those that benefited from HBOT survived on average for more than 3 years. The only factor significantly associated with improved wound healing and survival was diabetes. Conclusion: This retrospective analysis suggests a role for HBOT in the treatment of CUA with more than half of the treated patients benefiting and surviving for an average of more than 3 years. Summary at a Glance: Calciphylaxis is often a pre‐terminal event in dialysis dependent kidney disease, with obese and diabetic patients at highest risk. The role of hyperbaric oxygen therapy (HBOT) in the treatment of calciphylaxis has been unclear, with the therapy often being used as a last therapeutic resort. This paper is possibly the largest case series of HBOT use for the treatment of calciphylaxis and provides useful insights into its place in managing the disease.